A Marketing Perspective on Rebuilding Football’s Success - Yang, Haotian (Transactions on Economics, Business and Management Research, 2024)
In recent years, Beijing Guo’an Football Club (F.C.) has seen a significant deterioration in performance and fan involvement, indicative of a wider trend in Chinese football. During the money-driven era of soccer, Chinese football saw a significant influx of cash but ultimately faced financial strain and a decline in competitiveness, particularly during the COVID-19 epidemic. This study examines prospective solutions for Beijing Guo’an F.C. to tackle operational, management, and marketing difficulties. The analysis concentrates on the club’s performance statistics from 2014 to 2024, indices of fan involvement, and the factors contributing to the deterioration of management decision-making. The investigation revealed three primary emphasis points: alterations in management, performance outcomes in significant matches, and the disconnection between clubs and viewers. To address the highlighted issues, the proposal outlines a strategy for improving the club while retaining the management through marketing modifications and operational enhancements. Furthermore, communication and community initiatives may reestablish the bond among supporters. The paper helped to revitalize Beijing Guo’an F.C. and may also serve as a reference for other Chinese football teams in the intensifying worldwide competition.